The Detection of Mutational Changes in Sorghum using RAPD - T, Taryono; Cahyaningrum, Paramita (Indonesian Journal of Biotechnology, 2011)
Sorghum is a multifunction plant due to its high economic value as a source of food, feed and industrial raw material of biofuel. Sorghum improvement can be done through mutation breeding and this research was conducted to evaluate the power of mutation breeding by observing the difference between mutant and its original counterpart. Varieties of sorghum Durra, Zhengzu and their mutants B-100 and Zh-30 were arranged in completely randomized design. DNA extraction was done using a modified CTAB method. After purification, quantification, and dilution, PCR was carried out for RAPD analysis. The result showed that Durra and Zhengzu varieties were significantly different in plant height, number of leaves and seed colour, however the mutant and its original counterpart cannot be differentiated morphologically. RAPD can be used to differentiate mutant and its original counterpart by observing the specific band pattern from each primer.